Language variation in the Instagram discourse of Indonesian Papuan dialect - Mawene, Aleda; Handayani, Tri (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
The language variations and substance of Papuan millennials' speech on the Instagram platform are unique. The choice of language used reflects the fact of speaking Indonesian with a distinctive Papuan dialect. This study aims to describe language variation in Papuan dialect Indonesian instragram discourse. This research is categorized as qualitative-descriptive research with a socio-pragmatic approach. The study data are words, idioms, terms, and quoted sentences as well as features of Papuan millennials' Instagram discourse. The data is sourced from the Igers' accounts which are taken purposively and representatively. The researcher acts as an observer (silent reader /host follower). The data is analyzed inductively through the process of description, interpretation, and explanation. The research findings show that the orientation of language choices made by Papuan dialectal Indonesian Instagram account owners leads to four (4) patterns of language variation, namely: (1) patterns of Papuan dialectal Indonesian (IDP); (2) patterns of Indonesian (IL); (3) patterns of code-switching of Papuan dialectal Indonesian-Foreign Language (IDP